Trophic position and niche overlap of an Asian weatherfish (Misgurnus bipartitus), western tubenose goby (Proterorhinus semilunaris) and native benthic fish species - Pim Lemmers; Robin Olde Wolbers; Gerard van der Velde; Rob S. E. W. Leuven (Aquatic Invasions)
Co-occurring and morphologically similar species have adapted to differential niches to minimize competition. An invasive alien species can occupy an ‘empty niche’ in introduced ranges. Alternatively, the invader may occupy an overlapping niche and compete with native species to a certain degree. In a Western European lowland brook with high nutrient loads, we studied a benthic community of five fish species, including two alien species: an Asian weatherfish (Misgurnus bipartitus) and the western tubenose goby (Proterorhinus semilunaris). The native species concerned stone loach (Barbatula barbatula), spined loach (Cobitis taenia), and gudgeon (Gobio gobio). Because of the unknown effects of the invaders on native benthic fish species, the trophic position, isotopic niche overlap, and potential food competition among these species were identified using nitrogen and carbon stable isotopes. The trophic levels of the five fish species indicated that they are secondary consumers. The body size of native fish species correlated significantly negatively with their δ15N (‰) signature, in contrast with the invaders indicating that the latter are generalists. Significant isotopic niche overlap was observed among all benthic species. The degree of niche overlap of M. bipartitus was the highest with G. gobio (91.8%). Proterorhinus semilunaris showed the highest degree of niche overlap with B. barbatula (91.2%). It was notable that the observed niche overlap between the native B. barbatula and C. taenia was high (99.2%). Overlap between M. bipartitus and P. semilunaris was low (8.9%), indicating little resource competition between these alien species. Native species showed wider isotopic niches than the invaders. Bayesian mixing models revealed that native and alien species slightly differ in their main diet. The results suggest that the invaders are plastic in their resource use, leading to niche differentiation and promoting the co-existence of benthic fish species.